Effects of Aging Stereotype Threat on Working Self-Concepts: An Event-Related Potentials Approach - Zhang, Baoshan; Lin, Yao; Gao, Qianyun; Zawisza, Magdalena; Kang, Qian; Chen, Xuhai (Frontiers in Aging Neuroscience, 2017)
Although the influence of stereotype threat on working self-concepts has been highlighted in recent years, its neural underpinnings are unclear. Notably, the aging stereotype threat, which largely influences older adults’ cognitive ability, mental and physical health, did not receive much attention. In order to investigate these issues, electroencephalogram (EEG) data were obtained from older adults during a modified Stroop task using neutral words, positive and negative self-concept words in aging stereotype threat vs. neutral control conditions. Results showed longer reaction times for identifying colors of words under the aging stereotype threat compared to the neutral condition. More importantly, the negative self-concept elicited more positive late P300 amplitudes and enhanced theta band activities compared to the positive self-concept or neutral words under the aging stereotype threat condition, whereas no difference was found between these self-concepts and neutral words in the control condition. Furthermore, the aging stereotype threat induced smaller theta band synchronization and enhanced alpha band synchronization compared to the control condition. Moreover, we also observed valence differences in self-concepts where the negative self-concept words reduced early P150/N170 complex relative to neutral words. These findings suggest that priming stereotype threat could activate negative self-concepts as current working self-concept, and that this influence occurred during a late neural time course.